Unpacking linguistic features in EFL textbooks using systemic functional linguistics: Transitivity, Mood, and nominal group structure analysis - Hieronimus Canggung Darong; Maksimus Regus (East European Journal of Psycholinguistics)
Systemic functional linguistics provides a systematic and comprehensive approach to examining language use, offering valuable information about the construction of meaning in the context of experiential, interpersonal, and textual metafunctions. This framework can be used to examine linguistic features and discourse patterns of the EFL textbooks. This study analyzes the linguistic features that go into creating the metafunctions in question found in EFL textbooks using systemic functional linguistics. The study specifically focused on process types of Transitivity patterns, Mood structures, and nominal group structures. Data were taken from two secondary EFL textbooks published in 2013 by two Indonesian publishers from which samples of reading passages were purposefully chosen based on the topic, genre and difficulty, and they were modified into clauses for analysis. After transitivity analysis, material process type was found to be predominantly used signifying a focus on tangible actions. Furthermore, the mood structure predominantly employs declarative structures, indicating comprehensible and direct information exchanges. Nominal group analysis indicates that T (Thing) and DT (Deictic Thing) types are frequently used, increasing vocabulary with physical references. The pedagogical implications of the linguistic feature analysis provide tailored teaching-learning activities and the useful information for instructional design.